The innvestigation of the process streams integration in the multieffect evaporation plant for the concentration of sorghum syrup - Babak, Tatyana; Golubkina, Olga; Ponomarenko, Yevgeniya; Solovey, Ludmila; Khavin, G. L. (Технологический центр, 2018)
The study on the integration of heat streams of the evaporation station for sorghum syrup concentrating is presented. The relevance of the research is is why the research, aimed at reducing the consumption of external energy and enhancing operating efficiency, is relevant and has practical value. The main purpose of the work is to create a scientifically substantiated design with enhanced economic indicators of operation, ensuring saving in consumption of hot utility (steam) and cooling water. The problem was solved using the pinch-analysis. Heat streams, requiring heating and cooling, were identified, and the alternative project based on the selection of the value of minimum temperature difference ΔTmin, was created. This value was calculated and substantiated based on the data on thermal streams. The stream of condensate of return steam, the heat excess of which had not been used so far, was added to the system. For the alternative project, the layout of heat exchange equipment was proposed, calculation of plate heat exchangers was performed. The designed network of heat exchangers made it possible to decrease the annual steam consumption by 18 %. Cost-effectiveness analysis was conducted by comparing the indicators for two of the projects of the syrup preheating department for the evaporation station. The proposed alternative project saves power consumption of cooling water by 35.9 kW, of heating vapor steam – by 60.5 kW. At the interest rate of profit tax of 18 %, implementation of the alternative project will pay off in 4 months. As a result, net annual gain of an enterprise is planned to increase by 16 %, at virtually the same payback period of the projects. Application of the methods of heat streams integration made it possible to develop an effective project of sorghum syrup preheating before evaporation and ensure saving of external utilities.

Представлено дослідження інтеграції теплових потоків багатокорпусної випарної установки для концентрування сиропу сорго. Актуальність роботи визначається технологією процесу, який вимагає високих витрат енергії. Тому всі дослідження, спрямовані на зниження споживання зовнішньої енергії і підвищення ефективності роботи, актуальні і мають практичну цінність. Головною метою роботи є створення науково обґрунтованого проекту з поліпшеними економічними показниками роботи, забезпечення економії споживання гарячого теплоносія (пари) і охолоджуючої води. Рішення проблеми було проведено з використанням методу пинч-аналізу. Були ідентифіковані теплові потоки, що вимагають нагрівання та охолодження, і створений альтернативний проект, заснований на виборі значення мінімальної різниці температур ΔTmin. Це значення було розраховане і обґрунтовано на основі даних по тепловим потокам. У систему був доданий потік конденсату ретурної пари, надлишок тепла якого не використовувався досі. Для альтернативного проекту була запропонована схема розміщення теплообмінного обладнання, проведено розрахунок пластинчастих теплообмінників. Запроектована мережа теплообмінних апаратів дозволила знизити річні витрати пари на 18 %. Аналіз економічної ефективності проводився порівнянням показників для двох проектів відділення попереднього нагріву сиропу для випарної станції. Запропонований альтернативний проект забезпечує економію споживаної потужності охолоджуючої води 35,9 кВт, пари, що гріє – 60,5 кВт. При процентній ставці податку 18 % реалізація альтернативного проекту окупиться через 4 місяці. В результаті чистий річний дохід підприємства планується більше на 16 %, при практично однаковому терміні окупності проектів. Застосування методів інтеграції теплових потоків дозволило розробити ефективний проект попереднього підігріву сиропу сорго перед випаровуванням та забезпечити економію зовнішніх утиліт.
Keywords: energy recovery; pinch-analysis; evaporation plant; plate heat exchangers; sorghum syrup concentration; рекуперація енергії; пінч-аналіз; випарна установка; пластинчасті теплообмінники; концентрування сиропу сорго